2021
DOI: 10.3390/ijerph18020537
|View full text |Cite
|
Sign up to set email alerts
|

Participation Profile of Children and Youth, Aged 6–14, with and without ADHD, and the Impact of Environmental Factors

Abstract: Background: Children and youth with attention deficit hyperactivity disorder (ADHD) may experience difficulties in participation, but few studies examine their participation and the environmental factors affecting participation. This study explored the participation and the environmental factors of children and youth, with and without attention deficit hyperactivity disorder (ADHD), in the following three settings: home, school, and community. Materials and Methods: Parents of 65 participants aged 6–14 (M = 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Our study shows that students with disabilities, especially ADHD, were significantly more likely to be truant. This finding is congruent with previous results showing that involvement in school is lower among students having ADHD [ 41 ]. It is likely that negative attitudes towards people with disabilities may play a role in their school satisfaction [ 20 ], thus negatively affecting attendance at school.…”
Section: Discussionsupporting
confidence: 92%
“…Our study shows that students with disabilities, especially ADHD, were significantly more likely to be truant. This finding is congruent with previous results showing that involvement in school is lower among students having ADHD [ 41 ]. It is likely that negative attitudes towards people with disabilities may play a role in their school satisfaction [ 20 ], thus negatively affecting attendance at school.…”
Section: Discussionsupporting
confidence: 92%
“…“Supports” and “barriers” did not differ considerably across the three settings in our sample, a finding similar to that seen in children and adolescents with non-ASD disabilities (Bakaniene & Prasauskiene, 2020 ; Coster et al, 2011 ; Shabat et al, 2021 ). However, it is pointed to particularities at the home and the community setting:…”
Section: Discussionsupporting
confidence: 82%
“…Based on the International Classification of Functioning, Disability and Health (ICF) model, participation is defined as involvement in life situations and it has been highlighted that the role of participation as well as the role of context depends on personal characteristics and living environments ( World Health Organization, 2001 ). To the best of our knowledge, only one previous study has examined children with ADHD in respect of participation in all settings, including home, school, and community ( Shabat et al, 2021 ). It has been reported that children with ADHD are less involved in activities at home, school, and in community settings than children without ADHD, with a lower frequency of participation at home ( Shabat et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only one previous study has examined children with ADHD in respect of participation in all settings, including home, school, and community ( Shabat et al, 2021 ). It has been reported that children with ADHD are less involved in activities at home, school, and in community settings than children without ADHD, with a lower frequency of participation at home ( Shabat et al, 2021 ). However, there is still a substantial gap in knowledge regarding the long-term effects of the COVID-19 pandemic on home participation in children and adolescents with ADHD.…”
Section: Introductionmentioning
confidence: 99%